Public health and education spending in Ghana in 1992-98 : issues of equity and efficienty - Canagarajah, Sudharshan 1960- (Policy research working paper, 2001)
In an economy facing fiscal constraints, public spending in the social sectors needs to be linked to outcomes to ensure efficient and equitable delivery of services